The Effect of Paclobutrazol and Types of Nitrogen (N) Fertilizer on The Growth and Yield of Long Bean (Vigna sinensis L.) - Sari, Nirmala Aulia; Moeldjani, Ida Retno; Sulistyono, Agus (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
Long bean is the one of the most widely consumed vegetables both fresh and processed. The market demand for long beans is rising, but their production remains limited. This study aims to investigate how different concentrations of paclobutrazol and various types of nitrogen fertilizers affect the growth and yield of long bean plants. The research was conducted in Dander Village, Dander District, Bojonegoro Regency, East Java. The study employed a factorial Randomized Block Design (RBD) with two factors: the concentration of paclobutrazol (P0 = control, P1 = 150 ppm, P2 = 200 ppm, P3 = 250 ppm) and the type of nitrogen fertilizer (N0 = NPK control, N1 = Urea, N2 = ZA, N3 = KNO3). Variables to observed included plant length, number of leaves, flowering age, number of pods, pod weight, number of seeds, and fruit set. The results showed that the combination of 150 ppm paclobutrazol and KNO3 nitrogen fertilizer produced the best results in terms of the fastest flower emergence at 29 days after planting (HST) and the highest pod weight of long beans at 43.00 grams per plant. Keywords: Paclobutrazol, Various Nitrogen Fertilizers, Growth, Yield, Long Beans (Vigna sinensis L.)